Delay of Flowering at High Temperature in Chrysanthemum: Duration of Darkness and Transitions in Lighting Determine Daily Peak Heat Sensitivity - Nakano, Yoshihiro; Takase, Tomoyuki; Sumitomo, Katsuhiko; Suzuki, Shihori; Tsuda-Kawamura, Kana; Hisamatsu, Tamotsu (Horticulture journal, 2020)
Heat-induced flowering delay of Chrysanthemum morifolium is a major problem affecting the production of cut flowers in Japan. Understanding the delay mechanism is indispensable to achieve stable production. Heat sensitivity has been shown to fluctuate throughout the day, as if it is regulated by a circadian clock. This paper studied the involvement of a circadian clock and photoperiod in the fluctuation of heat sensitivity throughout the day by applying pulses of heat at different times to Chrysanthemum seticuspe and Chrysanthemum morifolium under different regimens of light and dark. One experiment examined the elevation of heat sensitivity under different photoperiods in order to determine whether the transition from light to dark or vice versa serves as a signal for a clock-like regulation of heat sensitivity. Maximum heat sensitivity was frequently observed at a constant interval after light-off, but not after light-on, identifying the transition to darkness as the signal that initiates the elevation mechanism. We also examined the descending phase of heat sensitivity. Heat sensitivity peaked approximately 16 h after light-off and then gradually declined under dark conditions, suggesting an endogenous clock-controlled fluctuation. We further studied the effect of light on elevated sensitivity by conducting trials with dark periods of 13 or 16 h. Sensitivity peaked at both 10–13 and 13–16 h after light-off under the 16 h-dark condition, but only at 10–13 h after light-off under the 13 h-dark condition, indicating a rapid decline in heat sensitivity induced by light supplied 13 h after light-off. Results of the three experiments suggest that the daily elevation in heat sensitivity is potentially controlled by an internal clock that is reset by a transition from light to dark. A subsequent transition to light appears to eliminate elevated sensitivity. From this, we conclude that heat sensitivity is maximized toward the end of the night, irrespective of photoperiod, in chrysanthemums.